1986
DOI: 10.1007/bf02140780
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional adjustment of adolescents extremely talented in verbal or mathematical reasoning

Abstract: Perceptions of self-esteem, locus of control, popularity, depression (or unhappiness), and discipline problems as indices of social and emotional adjustment were investigated in highly verbally or mathematically talented adolescents. Compared to a group of students who are much less gifted, the highly gifted students perceive themselves as less popular, but no differences were found in self-esteem, depression, or the incidence of discipline problems. The gifted students reported greater internal locus of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
7

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 35 publications
6
43
1
7
Order By: Relevance
“…In contrast, same-age placement is de rigueur in education. Repeatedly, acceleration has been found to be an optimal strategy for the intellectually enhanced child, as indicated both by cognitive outcomes (Benbow, 1991;Brody & Benbow, 1986;1987;Cox, Daniel, & Boston, 1985;Gross, 1993;Kulik & Kulik, 1984;Stanley & Benbow, 1983) and on measures of psychosocial adjustment such as peer acceptance and social identity Kulik & Kulik;Richardson & Benbow, 1991;. Nonetheless, it remains poorly supported among educators Southern, Jones, & Ficus, 1989;Start, 1988).…”
Section: Asynchrony As a "Self" Modelmentioning
confidence: 91%
“…In contrast, same-age placement is de rigueur in education. Repeatedly, acceleration has been found to be an optimal strategy for the intellectually enhanced child, as indicated both by cognitive outcomes (Benbow, 1991;Brody & Benbow, 1986;1987;Cox, Daniel, & Boston, 1985;Gross, 1993;Kulik & Kulik, 1984;Stanley & Benbow, 1983) and on measures of psychosocial adjustment such as peer acceptance and social identity Kulik & Kulik;Richardson & Benbow, 1991;. Nonetheless, it remains poorly supported among educators Southern, Jones, & Ficus, 1989;Start, 1988).…”
Section: Asynchrony As a "Self" Modelmentioning
confidence: 91%
“…The highly mathematically able students were also compared with a group achieving high verbal scores, and were found to experience fewer difficulties with peers than the verbal group. The highly verbally able students were more likely to perceive themselves as unpopular and there were other indications that higher verbal ability may be related to some social and emotional problems (Brody & Benbow, 1986;Dauber & Benbow, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…Not only was a high intelligence a benefit in the popularity stakes, but they concluded that "one can expect that more intelligent children are better social problem-solvers" (p. 186). Brody and Benbow (1986) used American SATs to compare mathematically and verbally high-scoring 13 year-olds with less highly achieving students. Questionnaires about their lives and feelings were mailed to them (response 78%), but the less-able comparison group were only included two years later.…”
Section: Friendshipmentioning
confidence: 99%